Participation in Pregnancy Class Increases Knowledge of Lactation Preparation among Pregnant Women - Nurulloh Oktavia Kartika Murti Wijayanti; Heny Astutik (FORIKES, 2026)
One factor contributing to the low rate of exclusive breastfeeding is the limited knowledge pregnant women have regarding lactation preparation. Pregnancy class is designed to serve as a learning medium to enhance their understanding of this topic. This research was conducted to analyzing the effectiveness of pregnancy class in inreaces knowledge of lactation preparation among pregnant women. The study employed an observational analytic method with a prospective approach and involved 30 pregnant women, who were selected using a multistage cluster random sampling technique from a total population of 78. Data were collected using a questionnaire on lactation preparation that had been adapted from prior studies. Descriptive analysis revealed that all participants who regularly attended the classes demonstrated good knowledge levels, while among those who were less active, two respondents (13%) still had only moderate knowledge. Data were analyzed using the Mann-Whitney test produced a p-value of 0.021 (<0.05), indicating a significant relationship between participation in pregnancy class and pregnant women’s knowledge of lactation preparation in Jabung District, Malang Regency. In conclusion, pregnancy class is effective in increases knowledge of lactation preparation among pregnant women.Keywords: pregnancy class; knowledge level; lactation preparation